2017
DOI: 10.1093/dote/dox056
|View full text |Cite
|
Sign up to set email alerts
|

Abdominal diameter index is a stronger predictor of prevalent Barrett's esophagus than BMI or waist-to-hip ratio

Abstract: Abdominal obesity is associated with gastroesophageal reflux disease (GERD) and Barrett's esophagus (BE). Increased body mass index (BMI) and waist-to-hip ratio (WHR) have been associated with BE. Abdominal diameter index (ADI, sagittal abdominal diameter divided by thigh circumference) was previously shown to be a more accurate predictor of incident cardiovascular disease compared to other measurements. Our aim is to examine whether abdominal diameter index was a more accurate predictor of prevalent BE compar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 29 publications
0
7
0
1
Order By: Relevance
“…However, our study showed no association between a higher BMI and the diagnosis of Barrett's esophagus, in correlation with our recent findings from the mouse model that Western diet is not only inducing obesity but also changing the gut microbiota and induces an accelerated inflammatory condition in the esophagus (34). Recently, the waist to hip ratio has been found to be more strongly associated with the risks of Barrett's esophagus and esophageal adenocarcinoma than BMI (35). However, waist and hip measurements were not assessed in this study.…”
Section: Discussionmentioning
confidence: 73%
“…However, our study showed no association between a higher BMI and the diagnosis of Barrett's esophagus, in correlation with our recent findings from the mouse model that Western diet is not only inducing obesity but also changing the gut microbiota and induces an accelerated inflammatory condition in the esophagus (34). Recently, the waist to hip ratio has been found to be more strongly associated with the risks of Barrett's esophagus and esophageal adenocarcinoma than BMI (35). However, waist and hip measurements were not assessed in this study.…”
Section: Discussionmentioning
confidence: 73%
“… 7 , 10 More recent data suggests that the waist-to-hip ratio and abdominal diameter correlate better with esophageal acid exposure and risk of Barrett’s esophagus than BMI does. 11 , 12 This evidence is further supported by the fact that patients who achieve weight loss report a decrease in GERD symptoms. 9 …”
Section: Discussionmentioning
confidence: 84%
“…As an example, it is known that the mechanical effect of obesity on lung function is strongly associated with the central distribution of body fat. This fact is well known in cardiovascular diseases and was recently discussed in other types of disorders such as Barrett esophagus [10] and insulin resistance [11]. Barret esophagus was also associated with a subphenotype of asthma and obesity.…”
Section: Obesity and Asthma: The Chicken Or The Egg? Clinical Insightmentioning
confidence: 76%